2021
DOI: 10.34069/ai/2021.45.09.18
|View full text |Cite
|
Sign up to set email alerts
|

Formation of prospective music art teachers’ readiness for inclusive educational activity

Abstract: The article reveals the current problem of Ukrainian and foreign education - the preparation of present-day teachers to get engaged with learners with special educational needs. The objective of the study is to highlight the results of theoretical and experimental research on the formation of prospective music teachers’ readiness for inclusive educational activities, which is the result of students` professional training, prospective bachelors of music, determined by the level of music mastery, psychological-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…For the realization of inclusive education, qualified, trained teachers are required, who include: teaching contents, methods, teaching tools, new technologies to work with special needs students (Fole, 2017). In this context, the use of music as an inclusive tool for effective teaching is of special importance, which offers equal opportunities, quality services and innovations during the learning process (Ovcharenko, Sysoieva, Samoilenko, Chebotarenko, & Bohianu, 2021).…”
Section: Music and Inclusive Educationmentioning
confidence: 99%
“…For the realization of inclusive education, qualified, trained teachers are required, who include: teaching contents, methods, teaching tools, new technologies to work with special needs students (Fole, 2017). In this context, the use of music as an inclusive tool for effective teaching is of special importance, which offers equal opportunities, quality services and innovations during the learning process (Ovcharenko, Sysoieva, Samoilenko, Chebotarenko, & Bohianu, 2021).…”
Section: Music and Inclusive Educationmentioning
confidence: 99%
“…Особливо сприятливі умови для опанування майбутніми вчителями музичного мистецтва цінностями етнокультури різних народів створює застосування етноспрямованого змісту вокальної підготовки майбутніх учителів музичного мистецтва та інноваційних методів, технологій музичного навчання. Педагог-музикант повинен бути компетентним і майстерно застосовувати інноваційні технології навчання для формування ціннісних орієнтацій учнів у сфері музичного мистецтва, ефективності розвитку їх загальних, музичних здібностей, активізації інтересу дітей до навчання музичному мистецтву (Ovcharenko, Sysoieva, Samoilenko, Chebotarenko & Bohianu, 2021).…”
Section: Ya Chystikovaunclassified
“…The success of the inclusion process depends on various factors such as the qualification and ability of the teachers ( Toomsalu et al, 2019 ; Ovcharenko et al, 2021 ) and their attitudes toward the inclusion of students with disabilities ( Leyser and Tappendorf, 2001 ). Ovcharenko et al (2021) found that prospective music teachers in Ukraine who received pedagogical instruction targeted toward teaching music in an inclusive setting were able to improve educational outcomes for their students more than teachers who had not received the instruction. Opertti and Brady (2011) and Carrington and MacArthur (2012) concluded that teachers’ attitudes play a vital role in successful inclusion.…”
Section: Introductionmentioning
confidence: 99%